SPORT PSYCHOLOGY: BUILDING MENTAL TOUGHNESS THROUGH ATHLETICS - Ismatov, Abdukodir (Журнал иностранных языков и лингвистики, 2025)
Sport psychology plays a crucial role in enhancing athletic performance by focusing on the mental and emotional well-being of athletes. One of its key components—mental toughness—is essential for athletes to remain focused, motivated, and resilient under pressure. This article explores how participation in sports contributes to the development of mental toughness, highlighting strategies such as goal setting, visualization, self-talk, and stress management techniques. Through examples from various sports disciplines, the article demonstrates how psychological training complements physical training and fosters confidence, perseverance, and emotional control. Understanding the psychological aspects of sports not only benefits elite athletes but also supports the growth and well-being of students, amateur players, and everyday individuals striving for personal excellence.